Tax Minimization sebagai Pemoderasi pada Pengaruh Exchange rate terhadap Transfer pricing - Sofyan Hadi Febrianto; Eni Srihastuti; Dewi Wungkus Antasari (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of exchange rate on transfer pricing with tax minimization as a moderating variable. The research employs a quantitative approach using secondary data obtained from companies’ financial statements. The analytical methods include regression analysis and interaction testing to examine the moderating role. The results indicate that tax minimization does not strengthen the effect of exchange rate on transfer pricing, but instead weakens the relationship, leading to the rejection of the second hypothesis (H2). These findings suggest that companies tend to rely more on tax efficiency strategies rather than responding to exchange rate fluctuations in determining transfer pricing policies. This study implies that internal company factors play a more dominant role than external factors in influencing transfer pricing decisions.